A User Centered Multi-Objective Handoff Scheme for Hybrid 5G Environments - Li Qiang; Jie Li; Touati, Corinne (IEEE transactions on emerging topics in computing, 2017)
In this paper, we propose a user centered handoff scheme for hybrid 5G environments. The handoff problem is formulated as a multi-objective optimization problem which maximizes the achievable data receiving rate and minimizes the block probability simultaneously. When a user needs to select a new Base Station (BS) in handoff, the user will calculate the achievable data receiving rate and estimate the block probability for each available BS based on limited local information. By taking the throughput metric into consideration, the formulated multi-objective optimization problem is then transformed into a maximization problem. We solve the transformed maximization problem to calculate the network selection result in a distributed method. The calculated network selection result is proved to be a Pareto Optimal solution of the original multi-objective optimization problem. The proposed scheme guarantees that based on limited local information, each user can select a new BS with high achievable data receiving rate and low block probability in handoff. Comprehensive experiment has been conducted. It is shown that the proposed scheme promotes the total throughput and ratio of users served significantly.